Do humans and nonhuman animals share the grouping principles of the Iambic - Trochaic Law? - de la Mora, Daniela M. (2013)
The Iambic-Trochaic Law describes humans’ tendency to form trochaic groups over sequences varying in pitch or intensity (i.e., the loudest or highest sound marks group beginnings), and iambic groups over sequences varying in duration (i.e., the longest sound marks group endings). The extent to which these perceptual biases are shared by humans and nonhuman animals is yet unclear. In Experiment 1, we trained rats to discriminate pitch-alternating sequences of tones from sequences randomly varying in pitch. In Experiment 2, rats were trained to discriminate duration-alternating sequences of tones from sequences randomly varying in duration. We found that nonhuman animals group as trochees sequences based on pitch variations, but they do not group as iambs sequences varying in duration. Importantly, humans grouped the same stimuli following the principles of the Iambic-Trochaic Law (Experiment 3). These results suggest an early emergence of the trochaic rhythmic grouping bias based on pitch, possibly relying on perceptual abilities shared by humans and other mammals as well, whereas the iambic rhythmic grouping bias based on duration might depend on language experience.